(untitled) (Dissertare, 2023)
University Social Responsibility (USR for its acronyms in English) requires evaluation to make correct decisions, which ensure the fulfillment of its mission and the generation of actions that support the achievement of the goals linked to the Sustainable Development Goals (SDG for its acronyms in English), under quality standards. The objective of this work is to analyze the importance of the evaluation of University Social Responsibility in the transformation of the higher education institutions functions (HEI for its acronyms in English) for their articulation with the SDG. The approach of the work is qualitative, with a documentary design, supported by the use of bibliographic review techniques. In this sense, a literature review was carried out using the search engines Google Academic and Scielo, among others. From the analysis of the sources consulted, it was derived that the evaluation of USR programs favors the introduction of adjustments in said programs, with a view to promoting compliance with the SDG, through the development of interactive processes between the institution and its environment, which allow the generation of innovative and relevant responses, in support of entrepreneurship and social initiatives.